A systematic literature review of mitigating cyber security risk - Kamarudin, Syafila; Tang, Lian; Bolong, Jusang; Adzharuddin, Nor Azura (Springer Science and Business Media LLC, 2023)
Increasing internet consumption and constant technological development, specifically smartphones, have led to an increasingly urgent need for cyber awareness. Generally, smartphone cyber security is an established field and has inspired numerous relevant studies. Unfortunately, most past studies lacked focus on cyber security research in the form of a systematic literature search of smartphone use by the worldwide community. Therefore, this study reviewed past studies on mitigating cyber security risk in highly technology-dependent communities using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines and the Web of Science, Scopus, ScienceDirect, and Google Scholar online databases. The search strategy yielded 23 articles in total for inclusion in the systematic analysis. The thematic analysis yielded three themes: awareness, knowledge, and behavior, which in turn revealed 10 sub-themes. Finally, recommendations were suggested for reference by future scholars.